Short- and mid-term effects of a parenting program on maternal well-being: Evidence for more and less advantaged mothers - Georg Camehl; Christa Katharina Spieß; Kurt Hahlweg (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper evaluates how a light-touch parenting program for parents of children below school entry age affects maternal well-being. We first analyze data from a randomized controlled trial focusing on more advantaged parents. Second, we use a sample of mothers from deprived neighborhoods, for which we generate a control group using additional data. Overall, results show a relatively large positive effect of the intervention on maternal well-being, with the largest effects appearing three years after treatment for both groups, while less advantaged families also experience a well-being increase directly after treatment. Mechanisms are further explored.
Keywords: I31; I26; J13; C21; C26; 330; Parenting Program; Family Well-being; Instrumental Variables; Triple P